RUMAH SINGGAH DIGITAL KOMUNITAS DESAIN - Rakha Winggal Prafitrarto; Tony Winata (Jurnal Sains, Teknologi, Urban, Perancangan, Arsitektur (Stupa), 2021)
Alternative forms of housing continue to develop along with the emergence of various problems from the massive vertical housing development in cities today, ranging from physical problems to the area to social problems among residents of vertical housing themselves. The domination of private space and the lack of public space has created a passive residential environment with minimal interaction. This has resulted in a lack of social control among residents who have made vertical housing a place that is prone to crime, such as several apartments in Jakarta which are known as locations for hidden prostitution, and even suicides. The city of Jakarta is one of the cities that has experienced massive vertical housing development. There needs to be a solution to solve settlement problems in the city of Jakarta through the scientific field of architecture with the concept of digital housing for communities. The purpose of this study is to implement the concept of digital shelter for communities supported by supporting theories oriented to human interaction in an architectural design object system in the form of vertical housing supported by digital equipment or technology. Keywords: Digital; Interactive; Living AbstrakAlternatif bentuk hunian terus berkembang seiring dengan timbulnya beragam permasalahan dari pembangunan hunian vertikal yang masif di perkotaan saat ini, mulai dari permasalahan fisik bangunan terhadap kawasan hingga permasalahan sosial di antara penghuni hunian vertikal sendiri. Dominasi ruang privat dan minimnya ruang publik telah menciptakan lingkungan hunian yang pasif dan minim interaksi. Hal ini menimbulkan kurangnya kontrol sosial di antara penghuni yang telah menjadikan hunian vertikal sebagai tempat yang rawan akan tindak kriminalitas, seperti beberapa apartemen di Kota Jakarta yang dikenal sebagai lokasi prostitusi terselubung, bahkan kasus bunuh diri. Kota Jakarta merupakan salah satu kota yang mengalami perkembangan hunian vertikal yang cukup massif. Perlu adanya solusi untuk menyelesaikan permasalahan permukiman di Kota Jakarta melalui bidang keilmuan arsitektur dengan konsep hunian digital untuk komunitas. Tujuan dari penelitian ini adalah mengimplementasikan konsep Hunian digital untuk Komunitas yang didukung oleh teori-teori pendukung yang berorientasi pada interaksi manusia di dalam sistem objek perancangan arsitektur berupa hunian vertikal yang di dukung dengan peralatan atau teknologi digital.